Multivariate Dynamical Sampling in ℓ2(ℤd) and Shift-Invariant Spaces. (26th April 2019) - Zhang, Qingyue; Li, Zunxian
Abstract: In this article, we mainly study the multivariate dynamical sampling inℓ 2 ( ℤ d ) and shift-invariant spaces. We first provide a sufficient and necessary condition forc ∈ ℓ 2 ( ℤ d ) which can be reconstructed by its spatial and temporal samples. Then we give a concrete example to show that the sufficient and necessary condition is feasible. Finally, we discuss the multivariate dynamical sampling problem in shift-invariant spaces.